2021
DOI: 10.3390/plants10050839
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anther Culture Media for Enhanced Callus Formation and Plant Regeneration in Rice (Oryza sativa L.)

Abstract: Anther culture technique is the most viable and efficient method of producing homozygous doubled haploid plants within a short period. However, the practical application of this technology in rice improvement is still limited by various factors that influence culture efficiency. The present study was conducted to determine the effects of two improved anther culture media, Ali-1 (A1) and Ali-2 (A2), a modified N6 medium, to enhance the callus formation and plant regeneration of japonica, indica, and hybrids of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 79 publications
0
36
2
1
Order By: Relevance
“…Androgenesis has been utilized to develop a number of rice varieties and improved breeding lines mostly in japonica cultivars [ 18 ]. However, indica cultivars was found to be recalcitrant to tissue culture including anther culture which hinders the success in rice improvement [ 19 , 20 ]. Anther culture is of two steps: the first step involves the induction of calli from microspores and the next step deals with the regeneration of green plants from the calli [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Androgenesis has been utilized to develop a number of rice varieties and improved breeding lines mostly in japonica cultivars [ 18 ]. However, indica cultivars was found to be recalcitrant to tissue culture including anther culture which hinders the success in rice improvement [ 19 , 20 ]. Anther culture is of two steps: the first step involves the induction of calli from microspores and the next step deals with the regeneration of green plants from the calli [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The onset and frequency of callus initiation is widely known as genotype dependent. It can be improved by adjusting culture media with different combination ratio of auxin and cytokinin (Rahman et al 2021), modified basal media (Ali et al 2021), or supplementing with polyamines (Maharani et al 2020). The present study suggested that gamma irradiation treatments indirectly could increase callus formation.…”
Section: Development Of Dhs Derived From M1 Plantsmentioning
confidence: 62%
“…The percentage of anthers producing callus increased with increasing irradiation dose which was 3.33%, 4.33%, 5.00%, and 5.67% at doses of 0, 100, 200, and 300 Gy, respectively (Table 1). In other studies, the percentage of callus induction of Indica rice cultivars was relatively in a similar range of 2.30%-8.45% (Ali et al 2021;Rahman et al 2021). Cempo Abang is classified as the Indica subspecies, which is known as more recalcitrant to callus induction in-vitro than the Japonica subspecies.…”
Section: Development Of Dhs Derived From M1 Plantsmentioning
confidence: 79%
“…Six Asian countries use over 89 percent of world rice produce viz., Bangladesh, Japan, China, Vietnam, Indonesia and India [36] . Rice is presently planted in over 100 nations, with a combined harvested area of around 158 million ha and about 470 million tonnes of processed rice generated [5] . To sustain the predicted 8.6 billion world population until 2030, yearly rice output of 756 million metric tonnes (MMT) is necessary to ensure food supply [10] .…”
Section: Introductionmentioning
confidence: 99%